Cementing material capable of improving toughness
By adjusting the mineral composition and particle grading of cement clinker, combining high-speed rail high-speed Beilite cement clinker and modified rubber powder, the particle size ratio of cement-based materials is optimized, the brittleness problem of cement-based materials is solved, and the brittleness problem of cement-based materials is achieved. The coordinated enhancement of the tensile strength and compressive strength of the material improves the toughness and crack resistance of the material.
Patent Information
- Application Number
- CN202411704656.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The brittleness problem of cement-based materials is mainly manifested in low tensile strength, which leads to cracks and cracks easily when the material is concentrated, affecting its service life and safety.
By adjusting the mineral composition of cement clinker, optimizing the grading of cement particles, and adding high-toughness auxiliary gelling materials, high-performance gelling materials with high strength and large folding pressure ratio are prepared. Specific measures include the use of high-speed rail high-grade Bellet cement clinker and modified rubber powder, and the optimization of the particle size ratio of each particle size combined with the accumulation model of Dinge-Funk continuous particle size distribution.
The coordinated enhancement of the tensile strength and compressive strength of cement-based materials is achieved, the toughness and crack resistance of the material are improved, the service life of the material is extended, the amount of clinker is reduced, and the cost is saved.
Smart Images

Figure BDA0005154245360000031 
Figure BDA0005154245360000061 
Figure FDA0005154245350000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementitious materials, and in particular to a cementitious material with improved toughness. Background Art
[0002] Cement-based materials have become the most widely used building materials in the world due to their high compressive strength, good durability and low price. However, with the development of engineering construction, especially with the continuous development of high-strength concrete, the brittleness of concrete has become an increasingly prominent problem. The fundamental reason is that the brittleness of concrete is caused by the low tensile strength of cement-based materials.
[0003] The tensile strength of cement-based materials is less than 1 / 10 of their compressive strength, and their ultimate tensile elongation is only 1.0×10 -4 MPa, these shortcomings of cement-based materials cannot be eliminated by self-improvement, and the use of "compounding" provides an effective solution to these problems. For example, adding high molecular polymer fibers to cement-based materials can significantly improve the early crack resistance of cement concrete, and adding steel fibers to cement-based materials can improve the compressive strength and tensile strength of cement concrete.
[0004] The Chinese patent "A method for preparing ultra-high performance fiber-reinforced cement-based composite materials" with publication number CN118271033A uses aggregate and fiber modification to prepare ultra-high performance fiber-reinforced cement-based composite materials, which improves the toughness and durability of concrete. In addition, polymer emulsion-modified concrete starts from the perspective of improving the performance of cementitious materials in concrete, providing an effective way to improve the toughness of concrete. High molecular polymers have some special functional groups that can coordinate with cement hydration products or metal ions to form special bridge bonds, further enhancing the bonding force between materials and improving the toughness of cement-based materials. The Chinese patent "A polymer in-situ toughened cement-based material and its preparation method" with publication number CN105819735A uses a method of combining polyvinyl alcohol and latex powder to prepare a cement-based material with good fluidity, good workability, fast strength development and high flexural strength.
[0005] The above toughening methods all have some limitations. Although traditional fiber toughening can improve the crack resistance of cement-based materials, it cannot inhibit the development of cracks from a microscopic perspective, and the toughening effect is limited. Although polymer toughening has a better effect and is currently the main means of cement-based toughening, polymer toughened cement-based materials also have problems such as uneven polymer distribution, poor compatibility and bonding, which affect their application in actual engineering. Summary of the invention
[0006] The purpose of the present invention is to provide a cementitious material with improved toughness. From the perspective of cement clinker, a high-performance cementitious material with high strength and large fold-to-compression ratio is prepared by adjusting the mineral composition of cement clinker, optimizing the cement particle grading, adding high-toughness auxiliary cementitious materials, etc., thereby fundamentally alleviating the problem of high brittleness of cement-based materials.
[0007] To achieve the above object, the technical solution adopted in the present invention is as follows:
[0008] A cementitious material with improved toughness comprises the following components in mass percentage: 9.2-16.2 wt% of a high-activity auxiliary cementitious material A, 49.4-53.5 wt% of a high-performance cementitious material B and 30.3-41.4 wt% of a high-toughness auxiliary cementitious material C, wherein the high-activity auxiliary cementitious material A is one or more of silica fume, slag or high-calcium fly ash, the high-performance cementitious material B is a high-iron phase high-belite cement clinker, and the high-toughness auxiliary cementitious material C is a modified rubber powder.
[0009] Furthermore, the mineral composition of the high-iron phase high-belite cement clinker is 32.07wt% C3S, 49.61wt% C2S, 1.96wt% C3A, and 16.36wt% C4AF.
[0010] The preparation method of the modified rubber powder is:
[0011] S1, adding quicklime to water to obtain saturated lime water;
[0012] S2. After cleaning the surface impurities of the rubber powder, put it into saturated lime water and soak it for 20 to 24 hours before taking it out;
[0013] S3, add MgCl2·6H2O to saturated lime water to obtain a mixed slurry, wherein Ca 2+ and Mg 2+ The concentration ratio is 1:1;
[0014] S4, heating the mixed slurry to 80°C and keeping it warm for 1 to 1.5 hours, stirring continuously during the heating and keeping warm process;
[0015] S5, adding the soaked rubber powder back into the mixed slurry and stirring continuously, the volume ratio of rubber powder to mixed slurry is 1:10, and then introducing CO2 gas, when the pH value of the mixed slurry drops to 7, stop aeration and stirring;
[0016] S6. Take out the rubber powder, wash it with anhydrous ethanol for several times, and then dry it to obtain modified rubber powder.
[0017] In S2, there is no limit to the amount of rubber powder added, as long as it is completely immersed in saturated lime water; in S5, the introduction rate of CO2 gas is 65L / (h·kgCa(OH)2).
[0018] Furthermore, the soaking time in S2 is 24 hours, the heat preservation time in S3 is 1 hour, and the drying in S6 is placed in a 60° C. oven for 5 to 6 hours.
[0019] Furthermore, the particle size of the highly active auxiliary gelling material A is in the range of 0.15 to 3 μm, and the median diameter D 50 It is 1.36μm.
[0020] Furthermore, the particle size of the high performance gelling material B is in the range of 3 to 32 μm, and the median diameter D 50 It is 16.78μm.
[0021] Furthermore, the particle size of the high-toughness auxiliary cementitious material C is in the range of 32 to 80 μm, and the median diameter D 50 It is 48.21μm.
[0022] Furthermore, the specific surface area of the high-toughness cementitious material is 360 to 380 m 2 / kg, the residue on 80μm square hole sieve does not exceed 5%; the initial setting time is not earlier than 15min, and the final setting time is not later than 45min; the water requirement is ≤30%, the 28d flexural strength is greater than 9.5MPa, the 28d compressive strength is greater than 45MPa, the 90d flexural strength is greater than 15MPa, the 90d compressive strength is greater than 70MPa, and the standard mortar flexural-compression ratio is not less than 0.20.
[0023] Furthermore, the mass percentages of the high-activity auxiliary gelling material A, the high-performance gelling material B and the high-toughness auxiliary gelling material C are calculated based on a Dinge-Funk continuous particle size distribution stacking model.
[0024] Furthermore, the calculation formula of the stacking model is as follows:
[0025]
[0026] In the formula, U(D P ) is the particle size D P The mass percentage of D P The particle size of high-activity auxiliary cementitious material A / high-performance cementitious material B / high-toughness auxiliary cementitious material C; D max is the particle size of the largest particle in the system, and D max The value is 80μm; D min is the particle size of the smallest particle in the system, and the D minThe value is 0.15 μm; n is the distribution index, and n is 0.24 to 0.5.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention optimizes the particle size distribution of cement clinker by adding two kinds of auxiliary cementitious materials. The high-activity auxiliary cementitious material A, which is a relatively fine cement particle (<3 μm), avoids the problem that the early strength development is too fast and easily leads to the later strength shrinkage, and optimizes the low degree of hydration; the high-toughness auxiliary cementitious material C, which is a coarse cement particle (32-80 μm) that only plays a filling role, avoids the waste of cement clinker, further reduces the amount of clinker used, and saves costs.
[0029] (2) The present invention incorporates two types of auxiliary cementitious materials with different particle sizes, namely, ultrafine high-activity auxiliary cementitious material A and large-particle high-toughness auxiliary cementitious material C. The two materials work together to achieve synergistic enhancement of strength and toughness from the material itself. This toughening method is different from fiber toughening and polymer toughening.
[0030] (3) The present invention divides the cementitious material into three particle size ranges and uses the Dinge-Funk continuous particle size distribution stacking model to optimize the particle size ratio, so that the cementitious material can be most densely packed, which not only ensures the density of the cement stone structure but also reduces the water demand of the cementitious material.
[0031] (4) The present invention utilizes saturated lime water to modify rubber powder, which not only utilizes the calcium hydroxide hydroxide ions in the saturated lime water to eliminate zinc stearate and the like on the rubber surface, thereby increasing the surface roughness of the rubber and improving the hydrophilicity of the rubber powder, but also utilizes the Ca(OH)2—CO2 gas-liquid reaction method to generate calcium carbonate whiskers on the surface of the rubber powder. Both the rubber powder and the calcium carbonate whiskers can improve the splitting tensile strength of cement-based materials. At the same time, as the age increases, the calcium carbonate whiskers will chemically react with the aluminum phase in the cement to generate calcium carbonate aluminate, which can improve the interface performance between the rubber powder and the cement stone, making the connection between the two closer. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] In the embodiment of the present invention, the high-activity auxiliary cementitious material A is one or more of silica fume, slag or high-calcium fly ash, the high-performance cementitious material B is high-iron phase high-belite cement clinker, and the high-toughness auxiliary cementitious material C is modified rubber powder.
[0034] In the embodiment of the present invention, the mineral composition of the high-iron phase high-belite cement clinker is 32.07wt% C3S, 49.61wt% C2S, 1.96wt% C3A, and 16.36wt% C4AF.
[0035] In the embodiment of the present invention, the preparation method of the modified rubber powder is:
[0036] S1, adding quicklime to water to obtain saturated lime water;
[0037] S2, clean the surface impurities of the rubber powder, put it into saturated lime water, soak it for 24 hours and then take it out;
[0038] S3, add MgCl2·6H2O to saturated lime water to obtain a mixed slurry, wherein Ca 2+ and Mg 2+ The concentration ratio is 1:1;
[0039] S4, heating the mixed slurry to 80°C and keeping it warm for 1.5 hours, stirring continuously during the heating and keeping warm process;
[0040] S5, adding the soaked rubber powder back into the mixed slurry and stirring continuously, then introducing CO2 gas, and when the pH value of the mixed slurry drops to 7, stopping the ventilation and stirring;
[0041] S6. Take out the rubber powder and wash it with anhydrous ethanol for several times, and then place it in a 60°C oven to dry for 5 to 6 hours to obtain modified rubber powder.
[0042] In the embodiment of the present invention, the particle size of the high-activity auxiliary gelling material A ranges from 0.15 to 3 μm, and the median diameter D50 is 1.36 μm.
[0043] In the embodiment of the present invention, the particle size of the high performance gelling material B is in the range of 3 to 32 μm, and the median diameter D50 is 16.78 μm.
[0044] In the embodiment of the present invention, the particle size of the high-toughness auxiliary cementitious material C is in the range of 32 to 80 μm, and the median diameter D50 is 48.21 μm.
[0045] Example 1
[0046] As a preferred embodiment of the present invention, this embodiment discloses a cementitious material with improved toughness, and its components are shown in Table 1.
[0047] Table 1
[0048] Components Mass% Highly active auxiliary gelling material A 9.2 High performance cementitious material B 49.4 High toughness auxiliary cementitious material C 41.4
[0049] Example 2
[0050] As a preferred embodiment of the present invention, this embodiment discloses a cementitious material with improved toughness, and its components are shown in Table 2.
[0051] Table 2
[0052] Components Mass% Highly active auxiliary gelling material A 10.6 High performance cementitious material B 50.6 High toughness auxiliary cementitious material C 38.8
[0053] Example 3
[0054] As a preferred embodiment of the present invention, this embodiment discloses a cementitious material with improved toughness, and its components are shown in Table 3.
[0055] Table 3
[0056] Components Mass% Highly active auxiliary gelling material A 12.9 High performance cementitious material B 52.1 High toughness auxiliary cementitious material C 35.0
[0057] Example 4
[0058] As a preferred embodiment of the present invention, this embodiment discloses a cementitious material with improved toughness, and its components are shown in Table 4.
[0059] Table 4
[0060] Components Mass% Highly active auxiliary gelling material A 16.2 High performance cementitious material B 53.5 High toughness auxiliary cementitious material C 30.3
[0061] Comparative Example
[0062] This comparative example is 42.5 ordinary Portland cement.
[0063] Standard mortar experiments were carried out on the high-toughness cementitious materials of Examples 1 to 5 and the comparative example. The specimen molding, curing, and strength test methods were carried out in accordance with the national standard "Cement Mortar Strength Test Method (ISO Method)" GB / T 17671. After the mortar specimens were cured for 28 days and 90 days, compressive and flexural strength tests were carried out. The test results are shown in Table 5 below.
[0064] Table 5
[0065]
[0066] As shown in Table 5, the flexural strength ratios of Examples 28d and 90d are better than those of ordinary 42.5 Portland cement, and the longer the age, the better the compressive strength. The compressive and flexural strength growth rates of the examples are higher than those of ordinary Portland cement, and their flexural strength ratios increase with increasing age, while the flexural strength ratio of ordinary Portland cement decreases, which indicates that the synergistic effect of high-belite cement clinker and the calcium carbonate whiskers on the surface of the modified rubber powder not only ensures the long-term strength of the high-toughness cementitious material, but also improves the toughness of the cementitious material.
[0067] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A cementitious material with improved toughness, characterized in that: The invention comprises the following components in mass percentage: 9.2-16.2 wt% of high-activity auxiliary cementitious material A, 49.4-53.5 wt% of high-performance cementitious material B and 30.3-41.4 wt% of high-toughness auxiliary cementitious material C, wherein the high-activity auxiliary cementitious material A is one or more of silica fume, slag or high-calcium fly ash, the high-performance cementitious material B is high-iron phase high-belite cement clinker, and the high-toughness auxiliary cementitious material C is modified rubber powder.
2. A cementitious material with improved toughness according to claim 1, characterized in that: The mineral composition of the high-iron phase high-belite cement clinker is 32.07wt% C3S, 49.61wt% C2S, 1.96wt% C3A, and 16.36wt% C4AF.
3. A cementitious material with improved toughness according to claim 1, characterized in that: The preparation method of the modified rubber powder is: S1, adding quicklime to water to obtain saturated lime water; S2. After cleaning the surface impurities of the rubber powder, put it into saturated lime water and soak it for 20 to 24 hours before taking it out; S3, add MgCl2·6H2O to saturated lime water to obtain a mixed slurry, wherein Ca 2+ and Mg 2+ The concentration ratio is 1:1; S4, heating the mixed slurry to 80°C and keeping it warm for 1 to 1.5 hours, stirring continuously during the heating and keeping warm process; S5, adding the soaked rubber powder back into the mixed slurry and stirring continuously, the volume ratio of rubber powder to mixed slurry is 1:10, and then introducing CO2 gas, when the pH value of the mixed slurry drops to 7, stop aeration and stirring; S6. Take out the rubber powder, wash it with anhydrous ethanol for several times, and then dry it to obtain modified rubber powder.
4. A cementitious material with improved toughness according to claim 3, characterized in that: The soaking time in S2 is 24 hours, the heat preservation time in S3 is 1 hour, and the drying in S6 is placed in a 60° C. oven for 5 to 6 hours.
5. A cementitious material with improved toughness according to claim 1, characterized in that: The particle size of the high-activity auxiliary gelling material A ranges from 0.15 to 3 μm, and the median diameter D 50 It is 1.36μm.
6. A cementitious material with improved toughness according to claim 1, characterized in that: The particle size of the high performance gelling material B is in the range of 3 to 32 μm, and the median diameter D 50 It is 16.78μm.
7. A cementitious material with improved toughness according to claim 1, characterized in that: The particle size of the high-toughness auxiliary cementitious material C is in the range of 32 to 80 μm, and the median diameter D 50 It is 48.21μm.
8. A cementitious material with improved toughness according to claim 1, characterized in that: The specific surface area of the high-toughness cementitious material is 360 to 380 m 2 / kg, the residue on 80μm square hole sieve does not exceed 5%; the initial setting time is not earlier than 15min, and the final setting time is not later than 45min; the water requirement is ≤30%, the 28d flexural strength is greater than 9.5MPa, the 28d compressive strength is greater than 45MPa, the 90d flexural strength is greater than 15MPa, the 90d compressive strength is greater than 70MPa, and the standard mortar flexural-compression ratio is not less than 0.
20.
9. A cementitious material with improved toughness according to claim 1, characterized in that: The mass percentages of the high-activity auxiliary gelling material A, the high-performance gelling material B and the high-toughness auxiliary gelling material C are calculated based on the Dinge-Funk continuous particle size distribution stacking model.
10. A cementitious material with improved toughness according to claim 9, characterized in that: The calculation formula of the stacking model is as follows: In the formula, U(D P ) is the particle size D P The mass percentage of D P The particle size of high-activity auxiliary cementitious material A / high-performance cementitious material B / high-toughness auxiliary cementitious material C; D max is the particle size of the largest particle in the system, and D max The value is 80μm; D min is the particle size of the smallest particle in the system, and the D min The value is 0.15μm; n is a distribution index, and n is between 0.24 and 0.5.
Citation Information
Patent Citations
Polymer in-situ toughened cement base material and preparation method thereof
CN105819735A
Preparation method of ultrahigh-performance fiber toughened cement-based composite material
CN118271033A
Preparation method of composite cement with low clinker dosage and high flexural compression ratio
CN101948255A
Green high-strength high-temperature-resistant multi-scale fiber reinforced rubber concrete and preparation method thereof
CN116217182A
Cementing material for low-alkali and fertilizer-efficiency slow-release vegetation concrete and preparation method of cementing material
CN117865525A
Cited By
High-crack-resistance low-carbon inorganic grouting material and formula design method thereof
CN121405425A